DYNAMIC MODELLING OF TOURISM ATTRACTION AND ENVIRONMENTAL CARRYING CAPACITY CASE STUDY: TAMAN BUNGA CIHIDEUNG AREA–WEST BANDUNG REGENCY - KUSTIWAN, IWAN; SAFRIANTY, ASTRI AULIA (ASEAN Journal on Hospitality and Tourism, 2012)
The development of agro tourism activities performed on protected area should be noticed aspects of the environmental carrying capacity. However, the fact is, agro tourism activities often followed by developments of other activities that impact on the conversion of agricultural land to uses other than agriculture. By taking the case in Taman Bunga Cihideung Area - West Bandung regency, this study was conducted using system dynamics modeling to examine the dynamics between tourist attractions with the carrying capacity of their environment. The system dynamics approach describes the problems on feedback processes. These feedbacks responsible for the changes that experienced over time which resulted dynamic behavior as consequence of system structure in agro tourism activities. Dynamic interaction of the elements of tourism attraction, socio-economic conditions of the population and carrying capacity are analyzed to understand the dynamic behavior. That dynamic behavior becomes meaningful and powerful to postulate phenomenon that occurs. The dynamic interaction between the elements of this system is used as a basis to simulate a variety of policy interventions that can develop tourism attraction with considering limitation of environmental carrying capacity. The study results can be used for sustainable tourism development policies.